Setninger i norsk og polsk – definisjoner og inndelinger - Janik, Marta Olga; Szymańska, Oliwia; Łukaszewicz, Barbara (Folia Scandinavica Posnaniensia, 2019)
In this article we give a brief summary of how Norwegian and Polish sentences are classified in the widely acknowledged grammar books. Therefore, we review the definitions of sentences in both languages, and compare the various classifications applied in Norwegian and Polish. Additionally, much focus is given to classification of sub clauses, which happen to be differently characterized in the respective languages. We would claim that there is a significant bias regarding features that determine classification of sub clauses in Norwegian and Polish. While in Norwegian a lot of emphasis is put on structural features, focusing on how particular units are organized within a sentence, the Polish classifications seem more semantic-oriented. As far as grammatical terms are concerned, Norwegian is featured by far more notions that might yield intransparency for a Polish learner or grammarian.  On the other hand, the Norwegian classifications seem far more transparent. Due to a lack of 1-1 relation between terms used in Norwegian and Polish, we cater for this need by providing terms applicable for both languages. We believe that this may come into useful for all who try to systematize their knowledge about sentences in both languages.